1989
DOI: 10.2214/ajr.153.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Interventional neurovascular treatment of traumatic carotid and vertebral artery lesions: results in 234 cases

Abstract: InterventionalNeuroradiology Section, 505 Pamassus Ave., L-352, San Francisco, CA 941 43. Address reprint requests to A. T. Higashida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(130 citation statements)
references
References 7 publications
3
123
0
2
Order By: Relevance
“…Endovascular techniques such as coil embolization and stent placement have gained increasing popularity in the treatment of blunt vascular injuries including pseudoaneurysm, fistula, and flow-limiting dissections. While some studies have raised concerns over the safety of endovascular techniques as a result of increased risks of stroke and stent occlusion 17,27,34 , other groups have reported good longterm results with endovascular treatment [35][36][37][38] . Specifically, endovascular occlusion has been advocated as a feasible and safe treatment for traumatic vertebral arteriovenous fistula 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular techniques such as coil embolization and stent placement have gained increasing popularity in the treatment of blunt vascular injuries including pseudoaneurysm, fistula, and flow-limiting dissections. While some studies have raised concerns over the safety of endovascular techniques as a result of increased risks of stroke and stent occlusion 17,27,34 , other groups have reported good longterm results with endovascular treatment [35][36][37][38] . Specifically, endovascular occlusion has been advocated as a feasible and safe treatment for traumatic vertebral arteriovenous fistula 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The direct surgical approach to the vertebral artery, on the other hand, also becomes extremely difficult and results in high risks due to the extensive periarterial plexus, a number of sources of collateral circulation, anatomical site and the risk of ischaemic attack and infarction of the vertebrobasilar system during its manipulation 3,10,16 . Recently, interventional neuroradiology employing endovascular techniques under local anesthesia has been described" 1,26 , with excellent results, and alterations in the neurological status of the patient may be observed when the vertebral artery is temporarily occluded using the balloon. This technique should always be considered for the resolution of these lesions because it reduces risks of surgery and its complications, by diminishing the hospital stay, as occurred in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Higashida et al [15] reported preservation of the parent artery in 88% of patients with TCCFs treated by using detachable balloons; other authors have described a need for parent artery occlusion in as many as 20% of cases [16,17].…”
Section: Review Of Endovascular Management Of Traumatic Carotid-cavermentioning
confidence: 99%